Podocarpus in the palaeogeographically complex island of Hispaniola: A stepping-stone colonization and conservation recommendations - Nieto Blázquez, María Esther (2021)
Aim: Hispaniola is the second largest island in the Caribbean and a hot spot of biodiversity. The island was formed by the fusion of a northern and southern palaeo-islands during the mid-Miocene (15 Ma). The historical split of Hispaniola together with repeated marine incursions during the Pleistocene is known to have influenced lineage divergence and genetic structure in a few birds and mammals, but the effect on vascular plants is less understood. The conifer genus Podocarpus has two species, P.hispaniolensis and P.buchii, that are endemic to the mountains of Hispaniola and are IUCN endangered. The former occurs in the mountains of the north, and the latter in the south, with a region of sympatry in the Cordillera Central. Here, we evaluate the historical split of the two palaeo-islands and repeated marine incursions as dispersal barriers to the geographical distribution of genetic diversity, genetic structure, divergence patterns and the historical demography of the two species. Location: Hispaniola island, Caribbean. Methods: Using genotyping-by-sequencing in 47 Podocarpus samples, we identified two sets of single nucleotide polymorphisms for our analyses (74,260 and 22,657 SNPs). We conducted a phylogenetic and an approximate Bayesian computation analysis to test evolutionary hypotheses of sympatric and allopatric speciation and stepping-stone colonization. Results: Podocarpus showed a population genetic structure that corresponds to the geographic distribution of the species. Podocarpus on Hispaniola fit a stepping-stone colonization model with bottlenecks at each mountain colonization event and speciation in Cordillera Central. Main conclusions: The historical events in question did not seem to have influenced the genetic structure, diversity or demography of Podocarpus; instead, the current geographic barriers imposed by lowland xeric valleys did. The clear divergence between species together with the elevated within-population genetic diversity and significant genetic structure calls for a multi-population in situ conservation of each species.